Anatomically resolved transcriptome and proteome landscapes reveal disease‐relevant molecular signatures and systematic changes in heart function of end‐stage dilated cardiomyopathy. Issue 1 (28th December 2022) - Lin, Ling; Liu, Shanshan; Chen, Zhangwei; Xia, Yan; Xie, Juanjuan; Fu, Mingqiang; Lu, Danbo; Wu, Yuan; Shen, Huali; Yang, Pengyuan; Qian, Juying
Abstract: Dilated cardiomyopathy (DCM), as characterized by the left ventricular dilatation and contractile dysfunction, is one of the molecular mechanisms of which are largely unexplored. Here, we profiled the region‐resolved transcriptome and proteome of healthy and DCM human myocardial tissue and obtained the deep‐coverage dataset consisting 7, 605 proteins and 19, 880 transcripts in four chambers of the human heart. On the basis of the core proteome and transcriptome characters of the healthy hearts, chamber‐specific proteome alterations were further revealed in end‐stage DCM, among which extracellular matrix (ECM), mitochondrial function, and muscle contraction were the most dysregulated biological processes. Protein–protein interaction network demonstrated divergent functional networks of DCM atrium and ventricle. Additionally, a 4‐biomarker panel (CTSB, vWF, C9, and MFGE8) was established with promising diagnostic potential for the DCM. Collectively, our data provide a global proteomic basis of the chamber‐specific cardiac tissue, and establish a protein catalog that holds promise for better definition and diagnosis of DCM. Abstract : Dr. Ling Lin has focused on developing multi‐omics pipelines for novel diagnostic biomarker discovery in clinical cohort of cardiovascular disease and human cancer. Dr. Lin completed her postdoctoral training in the laboratory of Dr. Pengyuan Yang at Fudan University where she investigated the altered lipid composition in hepatocellular carcinoma and identified novel mechanisms of palmitic acid to decrease cell membrane fluidity and limit glucose metabolism to induce tumor regression. Dr. Lin is currently working on defining the characterization of end‐stage dilated cardiomyopathy, and also on revealing stage‐specific homeostasis disruption of triple‐negative breast cancer.